Analisis RAPFISH Pada Studi Keberlanjutan Pembangunan Kawasan Wisata Heritage Kajoetangan di Kota Malang - Idris, Isnaeni Hasri; Narawida, Tania; Agustin, Rachma Dian; Oktaviani, Dinda; Hidayat, Muhammad Bilal (Brawijaya Journal of Social Science, 2023)
Kayutangan Heritage Tourism Village is one of Malang City's tourist villages, providing cultural tourism and historical education during the Dutch colonial time. This Kayutangan Heritage Tourism Village offers numerous potentials, including tourism that includes Dutch colonial art, local and international tourists' favorite culinary, and cultural and religious aspects. However, certain people from the local government and Pokdarwis Kayutangan remain skeptical about establishing the Kayutangan Heritage Tourism Village. Furthermore, the outbreak of the COVID-19 pandemic has resulted in a decrease in the number of tourists and the local community's income. This study aimed to analyze the sustainability aspects of the development of Kayutangan Heritage Tourism Village, which is reviewed from the economic, social, ecological, legal, and institutional dimensions. The research method used was Rapid Appraisal for Fisheries (RAPFISH) with Multi-Dimensional Scaling (MDS) coordination techniques. The study also used questionnaires distributed to 30 respondents. The results showed that the overall sustainability index value was 54.31, with a "fairly sustainable" category. The value of the sustainability index in the ecological dimension was 59.45, the social was 57.06, the institutional legal was 56.30, and the dimension was categorized as "quite sustainable". While the economic dimension had a value of 44.39, which was categorized as "less sustainable". Based on all the sustainability analysis results, the development of Kayutangan Heritage Tourism Village needs to pay attention to all dimensions considering that there are still obstacles to building tourist villages, such as improving coordination between managers and sustainably building tourism villages.